Water cooled turbocharger heat transfer model initialization: Turbine and compressor quasi-adiabatic maps generation. (25th February 2021) - Salameh, Georges; Goumy, Guillaume; Chesse, Pascal
Highlights: A thermal transfer model of a water-cooled gasoline turbocharger. Water cooling acts as a thermal barrier. The heat transfer models for the turbine and the compressor are independent. Quasi-adiabatic turbine and compressor maps are generated from supplier maps. Impeller inlet and outlet temperatures are calculated. Abstract: Water cooled turbochargers used in gasoline engines present a difficulty in studies due to heat transfers in both the turbine and the compressor. Data available for users is usually measured in stable operating conditions with high temperature gradients on the turbine side which affects the compressor and the whole turbocharger. The heat transfers between the different elements are not quantified. Heat transfer models are necessary to quantify the amount of heat exchanged with an element and calculate then the real amount of work produced or consumed. A lumped mass heat transfer model is presented in this paper where every element of the turbocharger is considered as a thermal mass. Three main elements are represented: the turbine, the compressor and the central housing. The heat transfer model is then used to generate compressor and turbine quasi-adiabatic maps using supplier maps and geometrical data without more complicated tests. An experimental campaign is conducted to validate the model and show the effect of the water cooling on the thermal transfer between the turbocharger elements. In this model, the compressor and the turbine are treated separately and the water cooling is considered as a thermal barrier between the two. No coupling between the compressor and the turbine heat transfer models is needed which simplifies the calculation compared to other models.